2022
DOI: 10.1038/s41598-022-17597-y
|View full text |Cite
|
Sign up to set email alerts
|

Postural control through force plate measurements in female AIS patients compared to their able-bodied peers

Abstract: The present understanding of the mechanisms responsible for postural deficit in adolescent idiopathic scoliosis (AIS) is still insufficient. This is important because some authors see one of the causes of this disease in the impaired postural control. Moreover, there is a reciprocal link between the level of postural imbalance and the clinical picture of these people. Therefore, we compared the center-of-pressure (COP) indices of 24 patients with AIS to 48 controls (CON) during four 20-s quiet stance trials wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…According to both sets of posturometric measurements, the scoliosis group exhibited greater spatial COP parameters (COP range of both medial–lateral and anterior–posterior displacement of the COP), and thereby greater sway area of the COP; however, there was no significant difference between the children with scoliosis and the controls in terms of the COP path length or COP velocity. These results are fully consistent with the findings of Gruber et al [ 18 ]; however, numerous studies have reported not only a greater COP range in the medial–lateral and anterior–posterior directions and sway area but also a greater sway path length in children/adolescents with scoliosis [ 5 , 10 , 12 , 19 , 20 ]. The enlarged values of spatial COP displacement parameters in both directions (medial–lateral and anterior–posterior occurring at normal excursions and COP velocity, as found in the present study) may result in large body oscillations in all directions and indicate decreased spatial postural stability in scoliosis patients [ 21 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to both sets of posturometric measurements, the scoliosis group exhibited greater spatial COP parameters (COP range of both medial–lateral and anterior–posterior displacement of the COP), and thereby greater sway area of the COP; however, there was no significant difference between the children with scoliosis and the controls in terms of the COP path length or COP velocity. These results are fully consistent with the findings of Gruber et al [ 18 ]; however, numerous studies have reported not only a greater COP range in the medial–lateral and anterior–posterior directions and sway area but also a greater sway path length in children/adolescents with scoliosis [ 5 , 10 , 12 , 19 , 20 ]. The enlarged values of spatial COP displacement parameters in both directions (medial–lateral and anterior–posterior occurring at normal excursions and COP velocity, as found in the present study) may result in large body oscillations in all directions and indicate decreased spatial postural stability in scoliosis patients [ 21 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, this method allowed us to distinguish children with asymmetric body weight overloading the convex side of their body from children with overload on the concave side. Because our research included children with scoliosis, these results fully confirmed previous reports on the effect of asymmetrical BWD on the BoS in children with IS when standing [ 4 , 5 , 6 , 7 , 14 , 17 ]. Although it would have been very interesting at this stage of our project research, it was not possible to identify any demographics or clinical characteristics that would determine the direction of overloading on the convex or concave sides of the body.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consider first the entropy, which was rather unexpectedly lower in VOL, i.e., showed a less irregular temporal structure of the HGRF time-series than in CON. Most studies using this measure to assess COP dynamics claim that increased, not decreased, irregularity indicates beneficial changes in postural control 9 , 24 , 25 . However, there is no shortage of authors who recognize the inverse relationship, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the desired features and postural skills have been confirmed, e.g. higher automaticity, better use of sensory signals, adaptability to changing environment and high exploratory capabilities 7 9 . Yet, it is not a completely consistent picture, and some doubts still arise.…”
Section: Introductionmentioning
confidence: 89%